2022
DOI: 10.2147/jaa.s395490
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemokines and Inflammatory Cells in Respiratory Allergy

Abstract: The idea of "one airway, one disease" has been gaining importance in the last decade. In the upper and lower airways, allergic mechanisms interact with each other. In the initial stage of respiratory allergic inflammation, allergens contact the respiratory epithelium, which produces chemokines and inflammatory factors, which cause allergic reactions by binding to the corresponding receptors and chemotactic various inflammatory cells to reach the epithelium and tissues. It also drives inflammatory cells to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 106 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…They participate in all of the three phases of AR by promoting inflammatory cell recruitment, differentiation, and allergic mediator release, and also be therapeutic targets for AR ( 36 ). The origin of chemokines and the inflammatory cells are different, but CCL and CXCL are two types of chemokines that are more closely related to the development of AR ( 37 ). Here, we found that 6 chemokines were significantly changed after GUANKE probiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They participate in all of the three phases of AR by promoting inflammatory cell recruitment, differentiation, and allergic mediator release, and also be therapeutic targets for AR ( 36 ). The origin of chemokines and the inflammatory cells are different, but CCL and CXCL are two types of chemokines that are more closely related to the development of AR ( 37 ). Here, we found that 6 chemokines were significantly changed after GUANKE probiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL1, CXCL5, and CXCL6 were markedly decreased, which receptor is CXCR2, expressed in neutrophils, monocytes, NK cells, mast cells, and basophils, and the main function is related to B cell lymphopoiesis and neutrophil trafficking. While CXCL11 was significantly increased, which receptor is CXCR3, expressed in Th1 cells, CD8+ T cells, and NK cells, and the main function is related to Type I adaptive immunity ( 37 ). Previous studies also showed that CCL4 and CCL23 were also significantly changed in AR patients ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry analysis of nasal turbinate biopsies taken from an AR patient six hours after an allergen challenge showed an increase in eosinophil infiltration, cell counts that expressed mRNA for IL-4 and IL-5, and expression of the lymphocyte chemokine receptors CCR3 and CCR4 (12) .…”
Section: Late Phase Of Allergen-induced Airway Inflammationmentioning
confidence: 99%
“…Epithelial cells and fibroblasts are important players in AR and other allergic diseases as they are equipped to respond to allergens or pathogen-associated molecular patterns (PAMP) and take part in immune response, namely by secreting chemokines and cytokines [18,19]. These chemokines and inflammatory factors bind to the corresponding receptors and chemotactic various inflammatory cells to reach the epithelium and tissues [20]. Interleukin-8/C-X-C motif chemokine ligand 8 (IL-8/CXCL8), macrophage inflammatory protein-1 alpha/C-C motif chemokine ligand 3 (MIP-1α/CCL3), and monocyte chemoattractant protein-1/C-C motif chemokine ligand 2 (MCP-1/CCL2) are inflammatory chemokines whose main function is to recruit neutrophils, macrophages, and monocytes to the site of injury or infection, respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…These chemokines and inflammatory factors bind to the corresponding receptors and chemotactic various inflammatory cells to reach the epithelium and tissues [20]. Interleukin-8/C-X-C motif chemokine ligand 8 (IL-8/CXCL8), macrophage inflammatory protein-1 alpha/C-C motif chemokine ligand 3 (MIP-1α/CCL3), and monocyte chemoattractant protein-1/C-C motif chemokine ligand 2 (MCP-1/CCL2) are inflammatory chemokines whose main function is to recruit neutrophils, macrophages, and monocytes to the site of injury or infection, respectively [20]. In allergic rhinitis, the chemokine IL-8 has been shown to increase in nasal secretions, after allergen challenge, although it may act in connection with other chemotactic factors in the recruitment of granulocytes [21,22].…”
Section: Introductionmentioning
confidence: 99%